Design, analysis and fabrication of dumb 4-axis left robot arm for education aids - Syed Shaharuddin, Syed Ahmad Haikal (2025)
In the realm of STEM education, this project introduces an innovative 4-axis robot arm designed to revolutionize robotics learning for students in Malaysia. Through hands-on experiences in constructing and programming real-world robotic systems, students will develop essential skills and ignite their passion for STEM disciplines.[1] Students in Malaysia lack hands-on experience in robotics, affecting their understanding of mechanical engineering and STEM concepts. Current teaching methods prioritize theory, leaving students unprepared for practical applications in STEM fields. Furthermore, students in Malaysia can be seen lack the motivation and drives to study based from the recent report on the number of student being absent during the SPM. Students nowadays lost interest in studying especially when it comes to theoretical learning There's a need for innovative tools to provide students with tangible experiences in constructing, programming, and operating real-world robotic systems, enhancing their skills and readiness for future careers in STEM[2]. The project objective is to analyse learning equipment's effectiveness. Therefore, a comprehensive evaluation will assess existing tools. Subsequently, the project focuses on designing an educational robot arm using SolidWorks software, integrating key mechanical engineering principles. Finally, the fabrication and assembly ensure functionality and educational relevance. Thus, completing the project's objectives. The methodologies employed in this project encompass a range of techniques vital for constructing and assembling the robot arm. Gluing will be utilized to secure components, while welding and cutting will be employed for metal fabrication and customization. Riveting will ensure structural integrity, while bending techniques will shape components as needed. Wiring and soldering will be essential for electrical connections, ensuring proper functionality and control of the robot arm. Additionally, coding will play a crucial role in programming the arm's movements and functionalities. Hopefully this project will result in a fully functional and educational robot arm, showcasing proficiency in real-world tasks. It will integrate mechanical engineering principles and coding expertise, enhancing students' understanding of robotics and preparing them for STEM careers.